2009
DOI: 10.5137/1019-5149.jtn.2785-09.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early bilateral decompressive craniectomy on outcome for severe traumatic brain injury

Abstract: AIM:Debate continues as to whether decompressive craniectomy (DC) is an effective treatment for severe traumatic brain injury (STBI). DC is mostly used as a second tier treatment option. The aim of this study was determined whether early bilateral DC is effective as a first tier treatment option in patients with STBI. MATERIAL and METHODS:The study compared two groups. Group 1 comprised 36 STBI patients for whom control of intracranial pressure (ICP) was not achieved with conservative treatment methods accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
1
32
0
2
Order By: Relevance
“…In our previous study, we compared 40 STBI patients who underwent early bilateral DC as a first-tier treatment with 36 patients in whom surgical treatment was considered as a second step. [25] In the early bilateral DC group, especially in patients <40 years and with an initial GCS score of ≥6, the favorable outcome rate was significantly higher. However, treatment is not clear in patients who suddenly develop bilateral pupillary dilation in the early posttraumatic period.…”
Section: Discussion Causes Of Pupillary Dilation In Patients Withmentioning
confidence: 99%
“…In our previous study, we compared 40 STBI patients who underwent early bilateral DC as a first-tier treatment with 36 patients in whom surgical treatment was considered as a second step. [25] In the early bilateral DC group, especially in patients <40 years and with an initial GCS score of ≥6, the favorable outcome rate was significantly higher. However, treatment is not clear in patients who suddenly develop bilateral pupillary dilation in the early posttraumatic period.…”
Section: Discussion Causes Of Pupillary Dilation In Patients Withmentioning
confidence: 99%
“…For example, seven studies reported that data was collected by neurosurgeons, trauma surgeons, physicians, nursing staff and research staff [7,[32][33][34][35][36][37] and the remaining studies did not report who conducted the assessments. Six studies reported conducting telephone interviews [7, 32, 34-37] and three studies also conducted face-to-face interviews [7,32,33]. One group retrospectively determined the condition of the patients using the GOS from the clinical records [38].…”
Section: Measurement Proceduresmentioning
confidence: 97%
“…The most widely used global outcome measure following DC is the the Glasgow Outcome Score (GOS [6,27,32,36,50,[56][57][58]). Although the GOS is widely used by neurosurgeons to assess functional outcomes following TBI, it has received criticism due to its susceptibility to systematic bias among different professional groups [39], poor interrater reliability [40], ambiguity within the upper classification categories due to multidimensional criteria and lack of sensitivity to change during the course of rehabilitation [59].…”
Section: Global Measures Of Physical Psychosocial and Cognitive Funcmentioning
confidence: 99%
“…In addition to these promising clinical results, new data suggested that complications of TBI may be reduced following early decompression [14][15][16][17].…”
Section: History Of Decompressive Craniectomymentioning
confidence: 99%